2004
DOI: 10.1001/archinte.164.13.1422
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Effect of Type 2 Diabetes Mellitus on Ischemic Heart Disease, Stroke, and Death

Abstract: In persons with type 2 DM, the risk of having an incident myocardial infarction or stroke is increased 2- to 3-fold and the risk of death is increased 2-fold, independent of other known risk factors for cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
349
4
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 571 publications
(383 citation statements)
references
References 17 publications
(17 reference statements)
19
349
4
11
Order By: Relevance
“…3 Mortality from cardiovascular disease may be up to four times higher in patients with T2DM. 4 The hypertension which typically accompanies T2DM appears to be the most significant contributor to this increased risk. 5 Endothelium derived nitric oxide (NO) is a potent vasodilator which plays a pivotal role in the moment to moment control of vascular tone.…”
Section: Introductionmentioning
confidence: 99%
“…3 Mortality from cardiovascular disease may be up to four times higher in patients with T2DM. 4 The hypertension which typically accompanies T2DM appears to be the most significant contributor to this increased risk. 5 Endothelium derived nitric oxide (NO) is a potent vasodilator which plays a pivotal role in the moment to moment control of vascular tone.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that patients with type 2 diabetes mellitus have a 2-to 3-fold higher risk of cardiovascular disease (CVD) and premature mortality vs the general population [1]. Measures of abdominal obesity, principally waist circumference, which more accurately describe the distribution of body fat than body mass index (BMI), are thought to be more closely associated with the risk of CVD and subsequent mortality [2].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] In populations free of cardiovascular disease at baseline, cardiovascular morbidity and mortality increased 1.5-to 3-fold in the presence of metabolic syndrome 10,[19][20][21] and two-to fourfold in the presence of type II diabetes. 22 In spite of the use of different and modified definitions, the metabolic syndrome is associated with more extensive vascular damage and increased risk for subsequent events in patients with prevalent cardiovascular disease. 12,23,24 In hypertensive patients without manifest vascular disease, the metabolic syndrome has been shown to be associated with increased intima-media thickness and left ventricular hypertrophy as well as with increased incidence of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%